أثر جائحة كورونا على مؤشرات الاقتصاد العالمي - الهرش، نافذ فايز أحمد (جامعة زيان عاشور بالجلفة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2020)
يهدف هذا البحث إلى إلقاء الضوء على آثار جائحة كرونا في الأسواق العالمية من خلال ثلاثة مؤشرات للاقتصاد العالمي: أسواق النفط، وأسواق الأسهم العالمية وأسواق السلع الدولية. من أهم النتائج التي توصلت إليها الدراسة: توجد علاقة ذات دلالة إحصائية عند مستوى معنوية (0.05) بين جائحة كورونا وكلا من: أسواق خامات النفط، وأسواق الأسهم العالمية، وأسواق السلع الدولية وكانت مؤشرات أسواق النفط الأعلى تأثرا بالجائحة تبعتها مؤشرات أسواق السلع، ثم مؤشرات أسواق المال. أوصت الدراسة ضرورة مراقبة مؤشرات أسواق النفط وأسواق السلع الدولية وأسواق الأسهم الدولية تباعا، وإلى اعتماد الذهب كخيار أو ملاذ آمن لأنه أثبت موثوقية عالية خلال الأزمة وإلى أهمية إنهاء عمليات الحجر الصحي ولو بشكل تدريجي لما لها من تأثير بالغ على أسواق النفط والسلع الدولية.
This research aims to shed light on the effects of the Corona pandemic in global markets through three indicators of the global economy: Oil Markets, Global Stock Markets and International Commodity Markets.Among the most important findings of the study: There is a statistically significant relationship at the level of significance (0.05) between the Corona pandemic and the markets of both : crude oil, global stock and international commodity .Indeed , the indicators of the oil markets were the most affected by the pandemic followed by commodity markets indices and then the financial market indices .The study recommended the necessity of monitoring the market indicators of oil markets, international commodity and international stock, respectively, as shown by the results of the study, and to the adoption of gold as an option or safe haven because it proved high reliability during the crisis and to the importance of ending quarantine operations, even gradually, because of their great impact on oil and financial markets.
Keywords: الاقتصاد العالمي -- الأسواق العالمية -- الأسواق المالية -- فيروس كورونا "كوفيد-19"